The Effect of Late Preterm Birth on Mortality of Infants with Hypoplastic Left Heart Syndrome - Attar, Mohammad A.; Dechert, Ronald E.; Schumacher, Robert E. (American Journal of Perinatology, 2012)
Objectives We evaluated the effect of late preterm (34 to 36 weeks' gestation) delivery on hospital mortality of infants with hypoplastic left heart syndrome (HLHS).Study Design Retrospective review of records of infants born at or after 34 weeks with no other lethal anomalies, cared for in a single tertiary perinatal center between 2002 and 2009. Factors associated with death prior to discharge from the hospital were ascertained using univariate and multivariate analyses.Results Of the 243 infants with HLHS, 35 were late preterm and 208 were ≥37 weeks (term). Using logistic regression analysis, late preterm delivery (odds ratio [OR] 2.95; 95% confidence interval [CI] 1.35 to 6.45), the presence of other major cardiac defects (OR 3.76; 95% CI 1.31 to 10.81), and the presence of noncardiac congenital anomalies (OR 6.13; 95% CI 1.43 to 26.22) were independently associated with hospital death.Conclusion Late preterm birth of infants with HLHS was independently associated with an increased risk of hospital death compared with those delivered at term.
Keywords: prematurity; complications; mortality; counseling; neonatal